Application of Electrodeposited Nano/Micro Structured Metal Oxide Thin Films for Liquefied Petroleum Gas Sensing - Bandara, K.N. D. (Faculty of Science, University of Colombo, 2018)
A gas sensor is a device utilized to caution us of dangerous gases. As one of foremost utilized household fuel, the detection of possible leakages of Liquefied Petroleum (LP) gas from production plants, from cylinders during their storage, transportation and usage is of utmost importance. This PhD thesis sets out to examine novel electrochemically fabricated, both ntype and p-type Cuprous Oxide (CU2O) thin films for the detection of LP gas. The effect of the electrical resistivity change of CU2O thin film layer in the presence of LPG was used for gas sensing. Nowadays, C112O thin films are receiving an intense interest from the Scientific Community, due to their morphology, electronic, optical properties, and low fabrication cost, non-toxic and easy to process as a thin film which make them a promising candidate for many industrial applications including new gas sensors for the detection of toxic species. The /7-type CU2O films were grown in an electrolytic bath containing a solution of sodium acetate and cupric acetate whereas chlorine-doped CU2O thin films were prepared by adding a cuprous chloride (CuCh) into an electrolytic solution containing lactic acid, cupric sulphate and sodium hydroxide. The type of conductivity of the deposited films was determined using spectral response measurements and Mott-Schottky plots. The surface morphological, structural and compositional variation of every sample were done by using Scanning Electron Microcopy (SEM) and Energy Dispersive X-Ray Spectrometry (EDX) analysis. To identify the quality of roughness and wetting behavior of films, Atomic Force Microscopy (AFM) images with statistical data of roughness and Contact angle measurements was used. The surface morphological, structural variation of /7-type CU2O thin films deposited in the acetate bath with the deposition time was studied through SEM analysis and EDX analysis and gas response of bare /7-type CU2O thin films was continued with 45 min deposited samples. The /7-type CU2O thin films showed a response resulting in a maximum response around 85 °C with - 4.1% of LPG response. To obtain the surface modifications for improvement of gas response, the surface of electrodeposited /7-CU2O thin films were modified by sulphidation using aqueous Na2S followed by (NHU^S vapor treatment. Compared to untreated thin films, the resultant films showed enhanced response to liquefied petroleum (LP) gas at a relatively low operating temperature (~45 °C) with - 45 % of LPG response, as one of the lowest reported for a cuprous oxide based material. X-ray diffraction spectra confinned that the films were of single phase. Observed by contact angle measurements and EDX data, (NI-LO2S vapor treatment converted the highly wetting sulphided films containing both Na and S to a partially wetting surface by forming sulphur on the film surface. This modification of the film surface, iv enabled the sensor response to recover to ambient level after stoppage of LP gas flow, which sulphidation alone was inapt.